Novel Cryopreservation Approach Providing Off-the-Shelf Availability of Human Multipotent Mesenchymal Stromal Cells for Clinical Applications - Olena Rogulska; Olga Tykhvynska; Olena Revenko; Viktor Grischuk; Svitlana Mazur; Natalia Volkova; Roman Vasyliev; Alexander Petrenko; Yuriy Petrenko (Hindawi Limited, 2019)
Cryopreservation is the only established method to provide long-term storage and fast availability of cellular product for therapeutic applications. The overwhelming majority of cryopreservation media contain toxic concentrations of dimethyl sulfoxide (DMSO) limiting the possibility for the direct administration of cryopreserved cells to the patients. Here, we propose a novel approach for nontoxic xeno-free cryopreservation of human multipotent mesenchymal stromal cells (MSCs) aimed at ensuring high viability, ready-to-use availability, and localized delivery of the cell-based graft into damaged tissues. For MSC cryopreservation, we applied sucrose pretreatment procedure and xeno-free cryoprotective medium containing human platelet-poor blood plasma (PPP), sucrose, and nontoxic concentration of DMSO. Using the combination of PPP, 0.2 M sucrose, and 1% DMSO, the recovery rate of cryopreserved MSCs reached 73% of the values obtained for noncryopreserved cells. Moreover, the presence of PPP in the cryoprotective medium provided the possibility to create a ready-to-use 3D hydrogel for the localized delivery and additional support of MSCs in vivo. In a proof-of-concept study, we assessed the regenerative capacity of cryopreserved MSCs in a full-thickness wound model in mice. The positive impact of MSCs within 3D gel on wound healing rates was confirmed by morphometric and histological examinations. Our results demonstrate the possibility to apply cryopreserved cells immediately after thawing using a cryoprotective medium as the vehicle solution.